Long-term survival of methotrexate in psoriatic arthritis - N. Battafarano; L. Rotunno; D. Mazzocchi; F. Desiati; G. De Marco; M. Ricci; A. Marchesoni (PAGEPress Publications, 2011)
Objective. The purpose of this study was to evaluate the long-term survival rate of Methotrexate (MTX) in the peripheral joint involvement of psoriatic arthritis (PsA) in a setting of everyday clinical practice. Methods. This was an observational restrospective study performed using the data from a dermatological-rheumatological PsA clinic. All of the patients evaluated at this clinic from March 1997 to December 2007 who were started on MTX alone, had a three-year follow-up time or had discontinued the therapy were included into the survey. Results. Of the 174 evaluable patients, 104 (59.8%) were still taking MTX after three years of treament. The reasons of therapy discontinuation in the remaining 70 (40.2%) patients were: 34 (19.5%) lost-to-follow-up, 18 (10.3%) adverse events, 14 (8%) inefficacies, and 4 (2.3%) deaths (none related to the therapy). MTX was effective in controlling joint inflammation but not in preventing their deterioration. Overall, adverse events were recorded in 43 patients (36.4% of the 114 patients with a three-year follow-up). No serious side effect occurred in the study population. Conclusions. The results of this study showed that, in a setting of clinical pratice, MTX had a good three-year performance in patients with peripheral PsA. Almost 60% of them were still taking this drug at the end of the study period and the toxicity was more than acceptable. In our opinion, MTX might be considered the non-biological DMARD of choice for the treatment of this condition. However it should be used earlier and at higher doses.